Genetic influences on cognitive endophenotypes in schizophrenia - Yeo, Ronald A. (Schizophr Res, 2014)
BACKGROUND: Cognitive deficits are prominent in schizophrenia and represent promising endophenotypes for genetic research. METHODS: The current study investigated the importance of two conceptually distinct genetic aggregates, one based on copy number variations (uncommon deletion burden), and one based on single nucleotide polymorphisms identified in recent risk studies (genetic risk score). The impact of these genetic factors, and their interaction, was examined on cognitive endophenotypes defined by principal component analysis (PCA) in a multi-center sample of 50 patients with schizophrenia and 86 controls. PCA was used to identify three different types of executive function (EF: planning, fluency, and inhibition), and in separate analyses, a measure general cognitive ability (GCA). RESULTS: Cognitive deficits were prominent among individuals with schizophrenia, but no group differences were evident for either genetic factor. Among patients the deletion burden measures predicted cognitive deficits across the three EF components and GCA. Further, an interaction was noted between the two genetic factors for both EF and GCA and the observed patterns of interaction suggested antagonistic epistasis. In general, the set of genetic interactions examined predicted a substantial portion of variance in these cognitive endophenotypes. LIMITATIONS: Though adequately powered, our sample size is small for a genetic study. CONCLUSIONS: These results draw attention to genetic interactions and the possibility that genetic influences on cognition differ in patients and controls.